Permainan Tradisional: Keterampilan Motorik dan Ketepatan Strategi - Ida Wahidah; Wulan Nurlaela; Cahyana Cahyana; Nurwahidah Nurwahidah; Firda Nafa'atur Rahman (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Traditional games in Indonesia are numerous and varied. Traditional games have many benefits. There have been many traditional games that are almost extinct and are no longer played by children nowadays. These types of games are Gobag and Baren. The purpose of this study was to determine the effect of the Gobag and Baren games on motor skills and the accuracy of strategies when playing these games. The case study research method was used in this research. Sampling is done by taking samples aged> 40 years. This is done because the sample in question is a person who has played this game. The number of samples is 12 people. Data were collected by means of interviews. The results of this study are motor skills and the accuracy of strategies in performing Gobag and Baren games. This is indicated by the better coordination ability between the eyes and feet, as well as the eye and the brain. In addition, the ability to estimate the direction for running so that you don't get caught is more precise.